JOB SATISFACTION SEBAGAI VARIABEL MEDIASI PENGARUH EMOTIONAL INTELLIGENCE TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Zalita Allena Putri; Sugeng Susetyo (Unib Press Universitas Bengkulu, 2021)
This research aims to determine and test Job Satisfaction to mediate the influence of Emotional Intelligence on Organizational Citizenship Behavior among employees at PT Bank Bengkulu. This type of research is a quantitative study using primary data through a questionnaire. The sample in this study was 142 employees of PT Bank Bengkulu who were collected using the census method. The results of this study explain that Emotional Intelligence has a significant positive effect on organizational citizenship behavior among employees of PT Bank Bengkulu. Emotional Intelligence has a significant positive effect on job satisfaction on employees of PT Bank Bengkulu. Job satisfaction has a positive and significant effect on organizational citizenship behavior among employees of PT Bank Bengkulu. Job satisfaction mediates Emotional Intelligence on organizational citizenship behavior.